Modeling of electron emission : its physics and novel applications - Wu, Lin (2009)
This thesis provides a deeper understanding of the physics behind the process of various electron emission mechanisms such as thermionic emission, photoemission, field emission and secondary electron emission, and explores its novel applications. The first topic is focused on the formulation of a nonequilibrium model to clarify the electron photo-field emission mechanism for an ultrafast laser excitation on a metallic surface under a dc biased voltage. The second topic is to study the reduction of shot noise for field emission including the effects of quantum partitioning, Coulomb repulsion and quantum correlation effects. The third topic is to use a statistical model to explain the occurrence of multipactor discharge due to secondary electron emission, and its high power absorption in a dielectric-loaded accelerating structure. For applications, we have proposed a new technique for low-temperature refrigeration based on thermal-field electron emission in a crossed-field gap.